Carbon Capture and Storage with a Focus on Capillary Trapping as a Mechanism to Store Carbon Dioxide in Geological Porous Media - Iglauer, Stefan (Benthem Science, 2011)
Carbon Capture and Storage (CCS) is a feasible short-to-medium term method to dispose carbon dioxide (CO2) which would otherwise be emitted into the atmosphere and cause potentially massively damaging climate change. In CCS, CO2 is captured, compressed and injected deep underground into geological formations. There are four main CO2 trapping mechanisms, namely stratigraphic or structural trapping, dissolution trapping, capillary trapping and mineral trapping. In this text we discuss all these trapping mechanisms with focus on capillary trapping, which has recently been identified as a rapid and reliable CO2 storage method.